2018
DOI: 10.1590/1807-57622017.0218
|View full text |Cite
|
Sign up to set email alerts
|

Narrativas de estudantes de Medicina e Enfermagem: currículo oculto e desumanização em saúde

Abstract: Um enfoque predominantemente biomédico atribuído ao ensino e à prática das Ciências da Saúde contribui para o processo de desumanização, que representa uma das principais queixas dos usuários dos sistemas de saúde em nosso país. Qualquer estratégia para enfrentar a questão depende da presença de profissionais de saúde bem formados de um ponto de vista técnico e humanístico. As maiores deficiências concernem à formação humanística. Este artigo constitui um recorte de um estudo cujo objetivo foi investigar a efe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
24

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 12 publications
1
4
0
24
Order By: Relevance
“…The individual who is a victim of a traffic accident requires integral health care; 12 however, the exclusivity of the biomedical model can dehumanize the care, as well as the lack of accountability and bond production. 28 Similarly to the findings of the present study's observation, in Colombia a study on the rights of the patients in relation to the services offered, revealed insufficient quality in the care provided, the patients being seen as sick and isolated organisms, bodies devoid of their singularity and restricted to technical-scientific knowledge that involves clinical experience, which increasingly distances them from their fundamental rights. 29 This research also reported the need for the professional to respect the patients, be cordial, and try to solve their physical or emotional problems, especially when they are most vulnerable, such as being victims of motorcycle accidents.…”
Section: Discussionsupporting
confidence: 75%
“…The individual who is a victim of a traffic accident requires integral health care; 12 however, the exclusivity of the biomedical model can dehumanize the care, as well as the lack of accountability and bond production. 28 Similarly to the findings of the present study's observation, in Colombia a study on the rights of the patients in relation to the services offered, revealed insufficient quality in the care provided, the patients being seen as sick and isolated organisms, bodies devoid of their singularity and restricted to technical-scientific knowledge that involves clinical experience, which increasingly distances them from their fundamental rights. 29 This research also reported the need for the professional to respect the patients, be cordial, and try to solve their physical or emotional problems, especially when they are most vulnerable, such as being victims of motorcycle accidents.…”
Section: Discussionsupporting
confidence: 75%
“…Além do denominado currículo formal, em todo ambiente de aprendizagem há o currículo velado, oculto, que se traduz tanto em práticas quanto em processos educativos e que levam a resultados de aprendizagem que não foram explicitados ou que são diversos dos desejados. Esse currículo oculto é fortemente influenciado pela cultura e pelas representações sociais tanto dos professores quanto dos alunos 27,28 , sendo percebido e reproduzido por esses educandos, como se nota em seus textos.…”
Section: Discussionunclassified
“…In the conceptual framework, the term "non-humanization", mentioned by the participants in this research, is equivalent to the understanding of the word dehumanization (2,4,15) , based on humanized work as the one that matches the assumptions of PNH, reinforcing its elements and commitments. Thus, what was contrary to humanization and its precepts was considered as dehumanization in this study.…”
Section: Discussionmentioning
confidence: 99%